2017
DOI: 10.4049/jimmunol.1601285
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and Overlapping Functions of TEC Kinase and BTK in B Cell Receptor Signaling

Abstract: The Tec tyrosine kinase is expressed in many cell types, including hematopoietic cells, and is a member of the Tec kinase family that also includes Btk. Although the role of Btk in B cells has been extensively studied, the role of Tec kinase in B cells remains largely unclear. It was previously shown that Tec kinase has the ability to partly compensate for loss of Btk activity in B cell differentiation, although the underlying mechanism is unknown. In this study, we confirm that Tec kinase is not essential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Importantly, phosphorylation of AKT is positively regulated by BTK [ 56 ]. The BTK family member TEC, which can partly compensate for BTK [ 57 ], may on the other hand limit the capacity of BTK to activate AKT [ 58 ].…”
Section: Btk In B Cell Receptor Signalingmentioning
confidence: 99%
“…Importantly, phosphorylation of AKT is positively regulated by BTK [ 56 ]. The BTK family member TEC, which can partly compensate for BTK [ 57 ], may on the other hand limit the capacity of BTK to activate AKT [ 58 ].…”
Section: Btk In B Cell Receptor Signalingmentioning
confidence: 99%
“…As such, we are currently evaluating the utility of these new molecules in B-cell related lymphocytic diseases where TECkinases play a prominent role. 17,51…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent study from our group showed that two pathways downstream of the BCR are involved in inactivation of the kinase GSK3 in chronic lymphocytic leukemia (CLL) cells, resulting in a different capacity of SYK, BTK, and PI3Kδ inhibitors to reduce the expression of the antiapoptotic protein Mcl-1, which is negatively regulated by GSK3 [ 20 ]. Finally, although BTK is located downstream of PI3K, several studies have suggested that there is also crosstalk in the opposite direction and that BTK can enhance the activity of the PI3K/AKT pathway in BCR-stimulated cells [ 21 , 22 , 23 , 24 , 25 , 26 ]. The mechanism behind this effect is still not completely understood, but involvement of BTK in the phosphorylation of the adaptor BCAP and in the production of the PI3K substrate PIP2 have been proposed as potential explanations [ 22 , 24 ].…”
Section: Bcr Signaling In Normal and Malignant B Cellsmentioning
confidence: 99%